Profound neuronal plasticity in response to inactivation of the dopamine transporter - Jones, Sara R. (The National Academy of Sciences, 1998)
The dopamine transporter (DAT) plays an important role in calibrating the duration and intensity of dopamine neurotransmission in the central nervous system. We have used a strain of mice in which the gene for the DAT has been genetically deleted to identify the DAT’s homeostatic role. We find that removal of the DAT dramatically prolongs the lifetime (300 times) of extracellular dopamine. Within the time frame of neurotransmission, no other processes besides diffusion can compensate for the lack of the DAT, and the absence of the DAT produces extensive adaptive changes to control dopamine neurotransmission. Despite the absence of a clearance mechanism, dopamine extracellular levels were only 5 times greater than control animals due to a 95% reduction in content and a 75% reduction in release. Paradoxically, dopamine synthesis rates are doubled despite a decrease of 90% in the levels of tyrosine hydroxylase and degradation is markedly enhanced. Thus, the DAT not only controls the duration of extracellular dopamine signals but also plays a critical role in regulating presynaptic dopamine homeostasis. It is interesting to consider that the switch to a dopamine-deficient, but functionally hyperactive, mode of neurotransmission observed in mice lacking the DAT may represent an extreme example of neuronal plasticity resulting from long-term psychostimulant abuse.